Swedish substrates suited for circular production of the edible gourmet mushroom maitake - Dahlin, Anna (2021)
A selection of locally sourced substrates were evaluated for hyphal growth and fruiting body production of the edible gourmet mushroom maitake (Grifola frondosa). Hyphal growth was evaluated on a wide range of substrates (30) including different leaves, sawdust and waste from food production and the substrate that performed best was potato peelings, which showed development of a remarkably dense mycelium.